Estimation of present-day inter-seismic deformation in Kopili fault zone of north-east India using GPS measurements - Prakash Barman; Jagat Dwipendra Ray; Ashok Kumar; J.D. Chowdhury; Kahsyap Mahanta (Geomatics, Natural Hazards & Risk, 2016)
Current study reports the present-day inter-seismic deformation of Kopili fault zone of north-east India and slip rate estimate of Kopili fault using five epochs of global positioning system (GPS) data collected from seven campaigns and five permanent sites. The rate of baseline length change of the GPS sites across the Kopili fault indicates ∼2.0 mm/yr E–W convergence across the fault. The fault parallel GPS site velocities clearly indicate dextral slip of the Kopili fault. The fault normal velocities show convergence across the Kopili fault, suggesting it to be a transpressional fault. The fault parallel velocities are inverted for fault slip and locking depth using an elastic dislocation model. The first-order, best-fit elastic dislocation model suggest average right lateral slip of 2.62 ± 0.79 mm/yr and a shallow locking depth (3 ± 2 km) of the Kopili Fault. The slip of the Kopili fault is contributing to seismic moment accumulation (∼70.74 × 1015 Nm/yr), sufficient to drive possible future earthquakes (Mw ≥ 5.17).